2019
DOI: 10.1183/23120541.00095-2019
|View full text |Cite
|
Sign up to set email alerts
|

A specific proteinase 3 activity footprint in α1-antitrypsin deficiency

Abstract: α1-Antitrypsin (α1-AT) deficiency is a risk factor for emphysema due to tissue damage by serine proteases. Neutrophil elastase (NE) has long been considered the enzyme responsible. However, proteinase 3 (PR3) also produces the pathological features of chronic obstructive pulmonary disease (COPD), is present in the same granules in the neutrophil and is inhibited after NE. We developed a specific footprint assay for PR3 activity and assessed its relationship to an NE footprint in α1-AT deficiency.An ELISA was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…Here, we used an assay to detect AαVal541 levels as a marker of PR3 activity based on principles described in previous studies [ 11 ]. We applied this assay to monitor levels of AαVal541 in between two doses of AAT, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we used an assay to detect AαVal541 levels as a marker of PR3 activity based on principles described in previous studies [ 11 ]. We applied this assay to monitor levels of AαVal541 in between two doses of AAT, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…We applied this assay to monitor levels of AαVal541 in between two doses of AAT, which has not been previously reported. Others showed that the PR3- and NE-specific fibrinopeptides were reduced after six months of weekly 60 mg/kg AAT augmentation [ 11 , 12 ]. Campos et al reported that the NE-specific fibrinopeptide AαVal360 showed a significantly stronger decrease in AATD patients who received 120 mg/kg weekly AAT infusion compared with those who received 60 mg/kg weekly AAT infusion [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PR3-specific fibrinogen epitope that is as promising and similar to Aα-Val360 is Aα-Val541. This fragment is also rather stable, can be measured in the blood of individuals, and is generated at the point of release of PR3 [ 62 ].…”
Section: Aat Augmentation Therapy and Its Alternativesmentioning
confidence: 99%
“…The study was successful in enabling collaboration between academic centres by providing recruitment and in-depth phenotyping of a group of patients with AATD and a wide range of physiological impairment to an agreed standard. All subjects also had plasma taken and stored for the development and validation of assays to monitor serine proteinase footprints 16 and other disease-specific biomarkers. In addition, the network provides baseline cohort data for long-term follow-up and importantly a well-characterised patient database for collaboration with industry (one of the key aims for the NIHR programme).…”
Section: Open Accessmentioning
confidence: 99%